Blood Urea Nitrogen as a Prognostic Marker in Severe Acute Pancreatitis. (29th March 2022) - Dai, Minhui; Fan, Yifei; Pan, Pinhua; Tan, Yun
Abstract : Rationale . Severe acute pancreatitis (SAP) is associated with high mortality rates. However, relatively little is known about its risk factors. Objectives . To explore independent risk factors with good and early predictive power for SAP severity and prognosis. Methods . Patients with SAP were enrolled at Central South University Xiangya Hospital between April 2017 and May 2021 and used as the training cohort. From June 2021 to February 2022, all patients with SAP were defined as external patients for validation. Patients were grouped by survival status at a 30-day posthospital admission and then compared in terms of basic information and laboratory tests to screen the independent risk factors. Results . A total of 249 patients with SAP were enrolled in the training cohort. The all-cause mortality rate at a 30-day postadmission was 25.8% (51/198). Blood urea nitrogen (BUN) levels were significantly higher in the mortality group (20.45 [interquartile range (IQR), 19.7] mmol/L) than in the survival group (6.685 [IQR, 6.3] mmol/L; P < 0.001 ). After propensity score matching (PSM), the BUN level was still higher in the mortality group than in the survival group (18.415 [IQR, 19.555] mmol/L vs. 10.63 [IQR, 6.03] mmol/L; P = 0.005 ). The area under the curve (AUC) of the receiver operating characteristic curve (ROC) of BUN was 0.820 (95% confidence interval, 0.721–0.870; P < 0.001 ). The optimal BUN level cut-off for predicting a 30-day all-cause mortality was 10.745 mmol/L. Moreover, patients with SAP were grouped according to BUN levels and stratified according to optimal cut-off value. Patients with high BNU levels were associated with significantly higher rates of invasive mechanical ventilation (before PSM: 61.8% vs. 20.6%, P < 0.001 ; after PSM: 71.1% vs. 32%, P = 0.048 ) and a 30-day all-cause mortality (before PSM: 44.9% vs. 6.9%, P < 0.001 ; after PSM: 60% vs. 34.5%, P = 0.032 ) than those with low BNU levels before or after PSM. The effectiveness of BUN as a prognostic marker was further validated using ROC curves for the external validation set (n = 49 ). The AUC of BUN was 0.803 (95% CI, 0.655–0.950; P = 0.011 ). It showed a good ability to predict a 30-day all-cause mortality in patients with SAP. We also observed similar results regarding disease severity, including the Acute Physiology and Chronic Health Evaluation II score (before PSM: 16 [IQR, 8] vs. 8 [IQR, 6], P < 0.001 ; after PSM: 18 [IQR, 10] vs. 12 [IQR, 7], P < 0.001 ), SOFA score (before PSM: 7 [IQR, 5] vs. 3 [IQR, 3], P < 0.001 ; after PSM: 8 [IQR, 5] vs. 5 [IQR, 3.5], P < 0.001 ), and mMarshall score (before PSM: 4 [IQR, 3] vs. 3 [IQR, 1], P < 0.001 ; after PSM: 5 [IQR, 2.5] vs. 3 [IQR, 1], P < 0.001 ). There was significant increase in intensive care unit occupancy in the high BUN level group before PSM (93.3% vs. 73.1%, P < 0.001 ), but not after PSM (97.8% vs. 86.2%, P = 0.074 ). Conclusions . Our results showed that BUN levels within 24 h after hospital admission were independent risk factors for a 30-day all-cause death in patients with SAP.